Saturday the rabbi went hungry eaudiobook Rabbi david small series, book 2. - Kemelman, Harry (Rabbi Small, 2013)
Rabbi Small returns in this New York Times–bestselling novel to investigate a mysterious death on the Day of Atonement The day before Yom Kippur, the synagogue sound system is on the blink, the floral arrangements are in disarray, and a member of Rabbi David Small's congregation—in the Massachusetts town of Barnard's Crossing—is terribly concerned with how much a Torah weighs. The rabbi is determined not to let these mundane concerns ruin his day of prayer and contemplation. But the holiest day of the Jewish year is interrupted when a member of the congregation is found dead in his car. Details emerge that suggest the man may have killed himself, but the rabbi's wife suspects murder. Which is it? Rabbi Small kicks into high detective gear to find out. His search for the culprit among the small town's cast of eccentric characters leads to nail-biting suspense in this highly entertaining and engrossing mystery.